The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12909-022-03461-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of good academic performance among university students in Ethiopia: a cross-sectional study

Abstract: Background Education plays a pivotal role in producing qualified human power that accelerates economic development and solves the real problems of a community. Students are also expected to spend much of their time on their education and need to graduate with good academic results. However, the trend of graduating students is not proportional to the trend of enrolled students and an increasing number of students commit readmission, suggesting that they did not perform well in their academics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 26 publications
5
50
0
3
Order By: Relevance
“…One year older than the average age reduces academic efficiency by 2%. These results are consistent with (Hoang et al, 2019;Tadese et al, 2022) who found a significant effect of children's age on academic performance. Results also show that being a male student raises academic efficiency by 1%, consistent with Delprato and Antequera (2021).…”
Section: Resultssupporting
confidence: 91%
“…One year older than the average age reduces academic efficiency by 2%. These results are consistent with (Hoang et al, 2019;Tadese et al, 2022) who found a significant effect of children's age on academic performance. Results also show that being a male student raises academic efficiency by 1%, consistent with Delprato and Antequera (2021).…”
Section: Resultssupporting
confidence: 91%
“…Pupils must dedicate a significant amount of their time to their studies in order to graduate with strong academic standing. Academically successful pupils are more likely to have better employment benefits, higher income, higher levels of self-confidence and self-esteem, lower levels of anxiety and depression, and lower rates of substance addiction (Tadese et al, 2022). Table 3 exhibits the test of the correlation between Pupils' Multimedia Based Instruction and Academic Performance.…”
Section: Resultsmentioning
confidence: 99%
“…According to self‐determination theory, when students' autonomy is supported, they are more likely to be competent and have positive learning outcomes (Ryan & Deci, 2017). Students' perceived competence in learning has also always been linked to better educational outcomes (Ryan & Deci, 2017), such as the final grade point average (GPA), which indicates how well the student performed academically throughout a program (Tadese et al, 2022). Several factors might influence the level of students' perceived teacher autonomy support and perceived competence in learning, such as students' gender.…”
Section: Introductionmentioning
confidence: 99%